On the importance of clarity in scientific advice for fisheries management. (January 2018) - Galland, Grantly R.; Nickson, Amanda E.M.; Hopkins, Rachel; Miller, Shana K.
Abstract: Fisheries management is a difficult process that requires policymakers and scientists to work in concert with one another to set quotas or other management actions that conserve fisheries resources for long-term use. Policymakers take such actions based on advice from their scientists, who serve as independent knowledge providers. There are many examples, however, of policymakers allowing short-term financial or political objectives to drive their decision making rather than strictly adhering to the advice of their scientists. Throughout the histories of the International Commission for Conservation of Atlantic Tunas and the Western and Central Pacific Fisheries Commission, policymakers have followed the advice of their scientists only 39% and 17% of the time, respectively. There are also a number of cases where a lack of clarity in the scientific advice leads to undesirable management actions, either a result of simple misinterpretation by policymakers or imprecision in the advice allowing for a range of actions not intended by the scientists. To improve the likelihood that managers and scientists interpret language in the same way, it is important that scientists provide advice that is explicit and precise and clearly states the appropriate management measures to be applied. Here, a set of guidelines that may help scientists to achieve the necessary clarity is presented. Following these steps would allow scientists to clearly describe stock assessment results and other complex scientific processes and provide their expert advice in a manner that is most useful for policymakers but without sacrificing their reputation of independent knowledge provision.